Hierarchical Time Series dengan ARIMA dalam Meramalkan Nilai Ekspor Indonesia - Hilmi Azzam Robbani; Marizsa Herlina (UNISBA Press, 2023)
Abstract. Export is a trade activity carried out between countries by carrying or sending goods originating from domestic areas abroad with the aim of being sold or marketed. Exports as a source of state revenue are needed for the Indonesian economy, because exports can make a major contribution to Indonesia's economic stability and growth. The value of exports that have decreased or increased for the future needs to be considered. The purpose of this study is to determine the ARIMA model and get the forecast results from the Hierarchical Time Series approach for Indonesian export value data. This forecasting method is used because Indonesia's export value data is a hierarchical time series data with two levels, namely level 0 (total export value of Indonesia) and level 1 (data on Indonesia's export value to ASEAN countries). The forecasting model used is ARIMA (Autoregressive Integrated Moving Average). For the selection of the best ARIMA model using the Mean Absolute Percentage Error (MAPE) value. The results showed that the forecast results of Indonesia's export value in June 2023 for Thailand amounted to 591 million USD, Singapore country amounted to 1,090 billion USD, for Malaysia country amounted to 712 million USD, for the Philippines country 981 million USD, for Myanmar country 83 million USD and the total export value of Indonesia amounted to 3,361 billion USD. Abstrak. Ekspor merupakan kegiatan perdagangan yang dilakukan antar negara dengan cara membawa atau mengirimkan barang yang berasal dari daerah dalam negeri ke luar negeri dengan tujuan dijual atau dipasarkan. Ekspor sebagai salah satu sumber pendapatan negara sangat dibutuhkan bagi perekonomian Indonesia, karena ekspor dapat memberikan kontribusi yang besar terhadap stabilitas dan pertumbuhan ekonomi Indonesia. Nilai ekspor yang mengalami penurunan atau peningkatan untuk masa yang akan datang perlu diperhatikan. Tujuan dari penelitian ini adalah mengetahui model ARIMA dan mendapatkan hasil ramalan dari pendekatan Hierarchical Time Series untuk data nilai ekspor Indonesia. Metode peramalan ini digunakan karena data nilai ekspor Indonesia merupakan data deret waktu hierarki dengan dua tingkatan, yaitu level 0 (total nilai ekspor Indonesia) dan level 1 (data nilai ekspor Indonesia ke negara-negara ASEAN). Model peramalan yang digunakan adalah ARIMA (Autoregressive Integrated Moving Average). Untuk pemilihan model ARIMA terbaik menggunakan nilai Mean Absolute Percentage Error (MAPE). Hasil penelitian menunjukkan bahwa hasil ramalan nilai ekspor Indonesia pada bulan Juni 2023 untuk negara Thailand sebesar 591 Juta USD, negara Singapura sebesar 1.090 Miliar USD, untuk negara Malaysia sebesar 712 Juta USD, untuk negara Filipina 981 Juta USD, untuk negara Myanmar 83 Juta USD dan total nilai ekspor Indonesia sebesar 3.361 miliar USD.